Community engagement in Indigenous food systems contamination studies: A systematic scoping review - Federico Andrade-Rivas; Hallah Kassem; Kira Mok; Chenoa Cassidy-Matthews; Matthew Little; Mélanie Lemire; Annalee Yassi; Jerry Spiegel (PLoS ONE, 2025)
Introduction Indigenous food systems are vital for maintaining cultural practices, physical and mental well-being, and community health. However, these systems are increasingly threatened by environmental contamination, exacerbating health disparities. Despite growing recognition of the importance of Indigenous knowledge in environmental health research, there is limited systematic evidence on how well community engagement is incorporated into studies investigating contamination of Indigenous food systems. This scoping review aims to assess reported practices for engaging Indigenous Peoples and the use of study results to support community-driven initiatives. Methods A systematic scoping review was conducted on peer-reviewed articles published between January 2010 and July 2024 that assessed contamination in Indigenous food systems with a human health dimension. The search included three databases: Web of Science, Scopus, and CAB Direct, yielding 2,203 articles. After applying inclusion and exclusion criteria, 202 studies were retained for final analysis. Data were extracted on study characteristics, community engagement strategies, Indigenous knowledge integration, and reported use of study results by Indigenous Peoples. The analysis was conducted using the PRISMA framework. Results Most studies (97%) employed quantitative methods, with fewer incorporating qualitative or mixed-method approaches. While community engagement was mentioned in about two-thirds of the studies, the depth of engagement varied significantly. A quarter of studies included Indigenous authors and only a small proportion reported meaningful collaboration with Indigenous Peoples throughout the research process. Studies with Indigenous authorship were more likely to report community engagement activities and utilization of results for broader community initiatives. Conclusion The increasing recognition of Indigenous and traditional knowledge within academia must extend beyond intellectual discourse to address health disparities. Indigenous Peoples have long advocated for self-determination and engagement in research conducted in their communities. As part of broader reconciliation efforts with Indigenous Peoples the environmental health scientific community must reciprocate these efforts by integrating discussions into scientific literature about community participation and implementation of study results. This review highlights the need for robust and meaningful community engagement in environmental health research related to Indigenous food systems.